2014
DOI: 10.1002/iid3.25
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophils in the blood of hematopoietic stem cell transplanted patients are activated and have different molecular marker profiles in acute and chronic graft‐versus‐host disease

Abstract: While increased numbers of eosinophils may be detected in patients with graft-versus-host disease (GVHD) following hematopoietic stem cell transplantation, it is not known if eosinophils play a role in GVHD. The aims of this study were to determine: whether eosinophils are activated during GVHD; whether the patterns of activation are similar in acute and chronic GVHD; and the ways in which systemic corticosteroids affect eosinophils. Transplanted patients (n = 35) were investigated for eosinophil numbers and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
(49 reference statements)
1
10
0
Order By: Relevance
“…On the other hand, there are some reports about an association between elevated concentration of eosinophils in PB and aGvHD; however, the association is still controversial, possibly due to the influence of corticosteroid therapy. [15][16][17]24,25 As mentioned in previous report from Basara et al, our results also showed that increased concentration of eosinophils in BM was associated with Figure 3. ROC curve for predicting severe aGvHD.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…On the other hand, there are some reports about an association between elevated concentration of eosinophils in PB and aGvHD; however, the association is still controversial, possibly due to the influence of corticosteroid therapy. [15][16][17]24,25 As mentioned in previous report from Basara et al, our results also showed that increased concentration of eosinophils in BM was associated with Figure 3. ROC curve for predicting severe aGvHD.…”
Section: Discussionsupporting
confidence: 88%
“…At the time of BM examination, 7 patients received corticosteroid therapy at a dose of 20 mg/day. [15][16][17][18][19][20][21][22][23][24][25][26][27] The median eosinophil concentration in BM was 1.1% (quartile 0.4-2.2%) and that in PB was 0.5% (0.0-2.0%). The intraclass correlation coefficient of eosinophil concentration in BM was 0.908 (95% CI 0.818-0.955, P o 0.001) and 0.911 (95% CI 0.816-0.957, P o0.001) for intra-and inter-observer variations, respectively.…”
Section: Patients Characteristicsmentioning
confidence: 99%
“…29,65 In spleens, frequency of total granulocytes was significantly reduced after B-I09 administration in the B10.D2 to BALB/c model (data not shown), in agreement with previous reports indicating that XBP-1 is critically involved in the differentiation and recruitment of granulocyte subsets into tissues leading to inflammatory fibrosis, 11,68,69 and that these subsets are involved in cGVHD. 70,71 Current leading therapies for cGVHD directly target B cells or T cells, 31,60 whereas the current study and previous literature suggest that inhibition of the IRE-1a/ XBP-1 pathway via B-I09 could directly impact other cell subsets involved in cGVHD development in addition to B cells and T cells, 65 such as dendritic cells, 10 granulocytes, 11 and even nonhematopoietic cells. 67 The ultimate goal of the HCT field is to cure cancers such as leukemia without producing deleterious GVHD.…”
Section: Org Frommentioning
confidence: 55%
“…Second, we only included HSC transplant recipients without systemic glucocorticoid treatment in our study. This choice was based on the fact that systemic corticosteroids promote eosinophilic apoptosis [32] and cause a general downregulation of cell surface markers on peripheral blood eosinophils in patients with GVHD [33]. By only including untreated patients, we eliminated HSC transplant recipients who suffered from more severe GVHD, making extrapolation of our findings to eosinophils from extensive chronic GVHD patients troublesome.…”
Section: Discussionmentioning
confidence: 99%